A novel and sensitive chemosensor based on a KMnO4–rhodamine B–CdS quantum dot chemiluminescence system for meropenem detection. Issue 2 (14th December 2016) - Khataee, Alireza; Lotfi, Roya; Hasanzadeh, Aliyeh
Abstract : The reaction of a KMnO4 –Rh B–l -cysteine capped CdS QD system is described as a novel chemiluminescence (CL) reaction. Meropenem exhibits a quenching effect on KMnO4 –Rh B–l -cysteine capped CdS QDs. Abstract : A sensitive and simple flow injection chemiluminescence (CL) system was constructed for the determination of meropenem, in which the CL intensity of the KMnO4 –rhodamine B (Rh B) reaction was enhanced in the presence of CdS quantum dots (QDs). A CL resonance energy transfer (CRET) occurs between CdS QDs as a donor and Rh B as an energy acceptor. Based on the strong specific quenching effect of meropenem on the CL intensity, a novel chemosensor for meropenem sensing was developed. Under the optimized conditions, the quenched CL emission intensity was proportional to the concentration of meropenem in the range of 0.002–10.0 mg L −1 with a detection limit (3 σ ) of 0.8 μg L −1 Moreover, the feasibility of the induced CL system was studied via the meropenem determination in environmental water samples.